America and the Cold War, 1941-1991 a realist interpretation - Graebner, Norman A.; Burns, Richard Dean; Siracusa, Joseph M. (Praeger, 2010)
What were the origins of the Cold War? What policies fueled it? Why did the Cold War perpetuate the nuclear arms race? How did it end? Who "won" the Cold War and why does it matter? The significance of the debate surrounding the answers to these questions makes for fascinating reading as it sheds light on the late 20th century--and its aftermath.